ZONAL METAMORPHISM AND PETROLOGY OF METAPELITES IN THE TIM-YASTREBOVSKAYA STRUCTURE, VORONEZH CRYSTALLINE MASSIF - Savko K.A.; Polyakova T.N. (My University, 2001)
Our detailed petrographic study of the Early Proterozoic metapelites of the Tim-Yastrebovskaya structure resulted in distinguishing the following four metamorphic zones: garnet-chlorite, staurolite-andalusite. staurolite-sillimanite, and sillimanite-muscovite. The zoning mapped in the area is noted for the fact that its Mn-rich metapelites contain the assemblage of Fe-Mn garnet with andalusite in place of staurolite. Based on its morphology, composition, and zoning, the garnet of the rocks can be subdivided into two types: early kinematic with prograde zoning and late kinematic with retrograde zoning or unzoned. The results of microthermometry and mineralogical thermobarometry led us to conclude that the metapelites of the Tim-Yas-trebovskaya structure were affected by two metamorphic events. During the early episode, which was related to folding at 2250 Ma, the metasediments were regionally metamorphosed to the garnet-chlorite grade (zone). The intrusion of large granodiorite bodies at 2086 Ma induced the second metamorphic episode, during which the metapelites were metamorphosed at 520-620 degreesC and 3-4 kbar.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой